2021
DOI: 10.1149/1945-7111/abde7c
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Nanoarrays Directly Grown onto a 3D-Carbon Felt Electrode as a Bifunctional Material for Garden Compost Microbial Fuel Cell

Abstract: The practical implementation of air-breathing microbial fuel cell (MFC) is critically linked to the development of efficient materials as cathode and electrochemically active biofilm-based anode. In this contribution, we demonstrate the feasibility by decorating a 3D carbon felt electrode with Pt nanoarrays (CF@Pt) as a bifunctional electrode material as efficient garden compost bioanode and airbreathing cathode. Half-cell electrochemical characterizations reveal that the onset potential of the anode reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Having a large surface area and excellent electrical conductivity, this binder-free nanoscale electrode was found to effectively promote the growth of electrochemically active bacteria and facilitate EET from bacteria to their host. 58 Sun et al 59 prepared gold-coated CP electrode for MFC, inoculated with S. oneidensis MR-1, the electricity production of MFC increased by 47% compared with naked CP electrode. Electrochemical cyclic voltammetry analysis and scanning electron microscopy observation revealed that the gold decorated CP electrode facilitated the formation of MR-1 biofilm.…”
Section: Modification Of Conductive Nanomaterialsmentioning
confidence: 99%
“…Having a large surface area and excellent electrical conductivity, this binder-free nanoscale electrode was found to effectively promote the growth of electrochemically active bacteria and facilitate EET from bacteria to their host. 58 Sun et al 59 prepared gold-coated CP electrode for MFC, inoculated with S. oneidensis MR-1, the electricity production of MFC increased by 47% compared with naked CP electrode. Electrochemical cyclic voltammetry analysis and scanning electron microscopy observation revealed that the gold decorated CP electrode facilitated the formation of MR-1 biofilm.…”
Section: Modification Of Conductive Nanomaterialsmentioning
confidence: 99%
“…Several EAB strains have been identified in a large variety of natural ecosystems such as marine sediments, soils, seawater, fresh water, domestic and industrial wastewater [20], activated sludge and sewage sludge [21]. Further other sources have been also reported as garden compost [22], manure [23], wetland [24] and mangrove [25]. All these ecosystems can be used as sources of primary inoculum for selection and isolation of EAB.…”
Section: Eab As Sensing Elementsmentioning
confidence: 99%
“…13 In another study, CF decorated with platinum nanoarrays increased the electron transfer efficiency exhibiting improved MFC performance. 14 MnCo 2 O 4 coated CF improved the electrochemically active electrode surface, resulting in improved power density than the bear CF anode. 15 Although conductive polymers (polyaniline and polypyrrole), metals (Pt, Ti, and Ag), and metal oxides (Fe 3 O 4 , MnO 2 , and Co 2 O 3 ) have been widely used for anode fabrication, however, such electrode materials present certain limitations.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, carbon felt (CF) modification with polyaniline enhanced the MFC power output 13 . In another study, CF decorated with platinum nanoarrays increased the electron transfer efficiency exhibiting improved MFC performance 14 . MnCo 2 O 4 coated CF improved the electrochemically active electrode surface, resulting in improved power density than the bear CF anode 15 .…”
Section: Introductionmentioning
confidence: 99%